2014
DOI: 10.1039/c4ra03820g
|View full text |Cite
|
Sign up to set email alerts
|

Vapour-based processing of hole-conductor-free CH3NH3PbI3 perovskite/C60 fullerene planar solar cells

Abstract: A new sequential-vapour-deposition method is demonstrated for the growth of high-quality CH 3 NH 3 PbI 3 perovskite films. This has enabled the all-vapour, low-temperature fabrication of hole-conductor-free planar perovskite solar cells consisting of only a CH 3 NH 3 PbI 3 /C 60 bilayer sandwiched between two electrical contacts, with a power conversion efficiency of 5.4%.Organometallic trihalide perovskites with the general formula (RNH 3 )MeX 3 (where R is an organic group, Me is Pb or Sn, and X is a halogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 20 publications
4
99
0
Order By: Relevance
“…The device shows a J SC , V OC , FF, and PCE of 14.83 mA/cm 2 , 0.79 V, 0.72, and 8.37%, respectively. To the best of our knowledge, this is the highest PCE for thermal-evaporated HTM-free perovskite solar cells with a perovskite layer deposited directly on TCOs [26,27]. Moreover, such a PCE is comparable and even a slight higher than some other recently reported HTM-free perovskite solar cells despite that an ultra-thin CH 3 NH 3 PbI 3ÀX Cl X layer is used here [21][22][23][24].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The device shows a J SC , V OC , FF, and PCE of 14.83 mA/cm 2 , 0.79 V, 0.72, and 8.37%, respectively. To the best of our knowledge, this is the highest PCE for thermal-evaporated HTM-free perovskite solar cells with a perovskite layer deposited directly on TCOs [26,27]. Moreover, such a PCE is comparable and even a slight higher than some other recently reported HTM-free perovskite solar cells despite that an ultra-thin CH 3 NH 3 PbI 3ÀX Cl X layer is used here [21][22][23][24].…”
Section: Resultsmentioning
confidence: 60%
“…Tsai et al [25] fabricated an inverted HTM-free PHJ perovskite solar cell with a PCE of 11.02% by a solution process. Hu et al [26] demonstrated an inverted HTM-free PHJ perovskite solar cell with a simple thermal evaporated perovskite/C 60 bilayer structure, which presented a PCE of 5.4%. Ng et al [27] reported that the PCE can be increased to 6.1% via adopting 4,7-diphenyl-1,10-phenanthroline (Bphen) as the hole blocking layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, dense and uniform perovskite films with increased grain size can be obtained after subsequent annealing. Besides one-step solution process, vapour deposition methods [71,72] and spraydeposition [26] were proposed. Perovskite films prepared by the vapour deposition methods are uniform and smooth with continuous coverage and excellent crystallinity.…”
Section: Preparation Methods Of 2d Perovskite Filmsmentioning
confidence: 99%
“…Other strategies to produce the active layer are based on MAPbX 3 deposition using vapor techniques, where the perovskite growth is carried out without using any solvent. In fact, several different vapor deposition techniques are reported in literature, showing better film uniformity and surface coverage of the active layer compared to the solution processed films [18,25]. However vapor deposition has some problems as the source temperature must be tightly controlled due to the relatively low thermal stability of the perovskite precursors.…”
Section: Introductionmentioning
confidence: 99%